2011
DOI: 10.1016/j.prp.2011.06.001
|View full text |Cite
|
Sign up to set email alerts
|

siRNA inhibition of aspartyl-asparaginyl β-hydroxylase expression impairs cell motility, Notch signaling, and fetal growth

Abstract: Introduction Aspartyl-asparaginyl-β-hydroxylase (AAH) regulates cell motility and invasiveness by enhancing Notch signaling. Invasive trophoblastic cells, which mediate placentation, normally express high levels of AAH. Previously, we showed that ethanol-impaired placentation is associated with reduced AAH expression. The present study determines the degree to which inhibition of AAH expression is sufficient to impair functions required for placentation. Methods Immortalized, first trimester-derived, human t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…Furthermore, as demonstrated in the present work, GBM cells transduced with Lenti-sh-ASPH resulting in sustained inhibition of ASPH expression, exhibited reduced viability and directional motility. Correspondingly, si-RNA [5, 6, 34] or antisense oligonucleotides [12, 35] targeting ASPH and not Humbug, inhibit cell motility. Although catalytic activity was not specifically demonstrated to be inhibited by the MO-Is in the GBM cells, the most important consequence of inhibiting hydroxylase activity, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, as demonstrated in the present work, GBM cells transduced with Lenti-sh-ASPH resulting in sustained inhibition of ASPH expression, exhibited reduced viability and directional motility. Correspondingly, si-RNA [5, 6, 34] or antisense oligonucleotides [12, 35] targeting ASPH and not Humbug, inhibit cell motility. Although catalytic activity was not specifically demonstrated to be inhibited by the MO-Is in the GBM cells, the most important consequence of inhibiting hydroxylase activity, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, gestational ethanol exposure impaired transformation of maternal decidual arteries such that the degree of impairment correlated with timing and duration of the insult, and severity of IUGR. The paradoxical response of glycogen cells may have been due to ethanol-inhibition of trophoblast cell motility and invasion [4,5,7]. Impaired motility of glycogen cells into the mesometrial triangle could account for their observed accumulation in the junctional zone.…”
Section: Discussionmentioning
confidence: 99%
“…Histological sections of placenta with underlying mesometrial triangle (5 µm thick) were immunostained with monoclonal antibody to Cytokeratin (CK) to detect invasive trophoblastic cells at the implantation site as previously described [5,23]. Briefly, deparaffinized and rehydrated tissue slides were incubated in preheated EnVision TM FLEX Target Retrieval Solution (high pH=9.0) for 20 minutes at 95-100°C.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 2 more Smart Citations